The effect of Puerariae radix on lipoprotein metabolism in liver and intestinal cells - Ho Nerissa; Mamo John; Lee Jeong-Sook; Pal Sebely (BMC, 2002)
Abstract Background Animal studies investigating the beneficial effects of Puerariae radix on cardiovascular disease have suggested this plant possesses anti-diabetic and lipid lowering properties. However, the exact mechanism by which Puerariae radix affects lipid metabolism is currently unknown. The aim of this study was to investigate the effect of the water extract of Puerariae radix on the secretion of VLDL and chylomicrons from HepG2 liver cells and CaCo2 cells, respectively, in humans. Methods The amount of apoB100 (a protein marker for VLDL) and apoB48 (a protein marker for chylomicrons) in cells and media were quantified by Western Blotting and enhanced chemiluminescence (ECL). Total, free and esterified cholesterol concentrations were measured by gas liquid chromatography. Results Treatment of cells with water extract of Puerariae radix significantly decreased apoB100 production and secretion from HepG2 cells up to 66% in a dose dependent manner. The intracellular total cholesterol and free cholesterol concentration in HepG2 cells also decreased with increasing concentration of the Puerariae radix. In contrast, water extract of Puerariae radix attenuated apoB48 concentrations in cells, but not apoB48 secretion from CaCo2 enterocytes. Conclusions Collectively, our findings suggest that the water extract of Puerariae radix attenuates the hepatic lipoprotein production and secretion. Our present cell culture findings may explain why circulating VLDL and LDL levels were attenuated in animals supplemented with Puerariae radix. Since decreasing the production and secretion of atherogenic lipoproteins decreases the risk of development of cardiovascular disease, diets supplemented with radix may provide a safe and effective beneficial cardioprotective effects in humans.